G494(P) Evaluation of efficacy and quality of child protection peer review. (25th October 2020) - Slater, J; Wong, S; Walker, V
Abstract : Aim: Peer review should be an established part of child protection practice in Trusts. There is guidance from the RCPCH and CPSIG. We undertook a service evaluation at a district general hospital using different data collection methods to evaluate quality and efficacy of the child protection medical (CPM) peer review process to ensure consistency and quality within the service. Method: 6 months of data from 01/07/2018 to 31/12/2018 were reviewed including cases via social care referral and ward admission, and data collected regarding: Timeliness of peer review discussion Outcomes e.g. communication with social care, change to report Perception of peer review and quality was also reviewed via a questionnaire to attendees Results: The questionnaire identified a positive perception of peer review; it was helpful and supported learning. Attendance was an issue due to clinical work pressures. Whilst most felt supported, there was still some anxiety about being critiqued in front of colleagues. Conclusion: Timeliness was an issue for discussion of CPM's. A case is not discussed if the consultant is not present and we suggested a nominated colleague feedback on their behalf. Acute cases were not always added for discussion. Dedicated admin, clear processes and support from the Named Doctor to appropriately run peer review is required. Peer review runs monthly, requiring 10 case discussions per meeting; current time of 60 minutes may need to increase but an efficiently run meeting is also vital. Dedicated time should be discussed as a team job planning priority. A small number of cases required further liaison but no significant concerns, which is a positive reflection of the quality and consistency of the CPM's. Child protection is recognised as a difficult area needing additional support and continued learning opportunities. Peer review of CPM's should provide this in a safe learning environment, acknowledging it does not replace supervision or evidence based courses and resources.